Poly-3-Hexylthiophene (P3HT)/graphene nanocomposite field-effect-transistor as ammonia detector - Tiwari S.; Singh A.K.; Balasubramanian S.K.; Takashima W.; Prakash R. (My University, 2025)
Poly-3-hexylthiophene (P3HT)/Graphene nanocomposite based field-effect transistor was fabricated, characterized and further used for the application of ammonia gas detection. Graphene as nanofillers in polymer matrix may provides large surface area for adsorbents and interactions with gas molecules, so, graphene act as an excellent gas sensing candidate applicable in organic sensor devices. Here, fabricated P3HT/Graphene active channel based field-effect transistors (FETs) were placed in ammonia gas environment for a range of concentrations (0.25 to 25 ppm) to discover this device as sensor, at room temperature. Device key performances parameters like drain current, threshold voltage and mobility in absence and presence of ammonia was examined. It was found that the device key parameters (calculated in absence of ammonia) were changed significantly as device was exposed into various concentrations of the ammonia gas. The structural morphology of the developed nanocomposite was also studied under scanning electron microscope. The P3HT/Graphene nanocomposite based OFET demonstrated excellent sensitivity of ammonia at room temperature with better reversibility and reproducibility in comparison to alone polymers (P3HT) based devices. Copyright © 2016 American Scientific Publishers.